Migrating from print and blended to fully online delivery: Its impact on faculty at an ODeL higher education institution - Moleko, Gabaiphiwe; Gumbo, Mishack (International Education Trend Issues, 2025)
This article, extracted from the first author’s doctoral study, describes faculty's experiences in an open distance e-learning (ODeL) institution implementing rapid changes in the delivery of teaching and learning. The University of South Africa (Unisa) was selected as the case study site. Chaos theory was chosen to frame our thinking about the impact of a slight change in a system. The study targeted the faculty in two colleges. Individual interviews were conducted with 10 faculty members. Atlas.ti was used to analyse the data. The data revealed that migrating to online delivery was necessary, quick and unorganised. It had many implications for the faculty. The article contributes knowledge about an ODeL institution like Unisa adapting to the demands of the 4IR, especially fuelled by COVID-19. Recommendations are made for the institution to address workload issues and implement a change management process that recognises the impact of change on the faculty.